2013
DOI: 10.1038/bjc.2013.580
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy plus regulatory T-cell depletion produces immunity against a mouse tumour that expresses a self-antigen

Abstract: Background:Photodynamic therapy (PDT) can lead to development of antigen-specific immune response and PDT-mediated immunity can be potentiated by T regulatory cell (Treg) depletion. We investigated whether the combination of PDT with cyclophosphamide (CY) could foster immunity against wild-type tumours expressing self-antigen (gp70).Methods:Mice with CT26 tumours were treated with PDT alone or in combination with low-dose CY. T regulatory cell numbers and transforming growth factor-β (TGF-β) levels were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 44 publications
4
66
0
1
Order By: Relevance
“…Only mice with CT26.CL25 tumours expressing the tumour antigen b-galactosidase could be cured and acquired immune memory [26]. Cures in BALB/c mice bearing CT26 tumours with verteporfin-PDT required the preliminary administration of cyclophosphamide, an anti-cancer drug that selectively depletes Treg cells in mice, and this combination produces a greater local oedema than PDT alone [27]. Vascular-PDT with WST11 resulted in cure of 70% BALB/c and 19% BALB/c nude mice with implanted CT26 tumours [21].…”
Section: Discussionmentioning
confidence: 99%
“…Only mice with CT26.CL25 tumours expressing the tumour antigen b-galactosidase could be cured and acquired immune memory [26]. Cures in BALB/c mice bearing CT26 tumours with verteporfin-PDT required the preliminary administration of cyclophosphamide, an anti-cancer drug that selectively depletes Treg cells in mice, and this combination produces a greater local oedema than PDT alone [27]. Vascular-PDT with WST11 resulted in cure of 70% BALB/c and 19% BALB/c nude mice with implanted CT26 tumours [21].…”
Section: Discussionmentioning
confidence: 99%
“…92 Reginato et al showed that the depletion of T-regulatory cells could potentiate PDT-mediated immunity. 93 …”
Section: Enhancing Antitumor Immunitymentioning
confidence: 99%
“…As a result, this model is prone to tumor relapse after VPDT although the tumor itself expresses the tumor antigen gp70. 41 It has been reported that verteporfin-VPDT could achieve tumor-free survival together with an induction of immunological memory (i.e., a complete response) in cell lines that bear a tumor rejection antigen, for example, RIF-1 tumors with EGFP in C3H/HeN mice, P815 tumors with P1A antigen in DBA/2 mice, or with the depletion of Treg cells in J774 tumors in BALB/c mice. 31,42,43 However, when CT26 tumors were treated with verteporfin, a complete response could be achieved only when repetitive low doses of cyclophosphamide were administered to deplete the Treg population.…”
Section: Discussionmentioning
confidence: 99%
“…31,42,43 However, when CT26 tumors were treated with verteporfin, a complete response could be achieved only when repetitive low doses of cyclophosphamide were administered to deplete the Treg population. 41 Alternatively, an additional foreign antigen, such as b-galactosidase, must be transfected into the tumor cells to strengthen its immunogenicity before the treatment. 45 In contrast, some other PSs (for example, hypericin and WST11 13,30 ) could trigger a complete response in the CT26 tumor model without the aid of extra immunomodulatory agents.…”
Section: Discussionmentioning
confidence: 99%